Pilgrimage Tourism Satisfaction with Reference to Prayagraj and Varanasi: An Empirical Study - Sharma, Ritesh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper the researcher find out the relationship between the tourists and pilgrims visiting Prayagraj and Varanasi and their overall satisfaction. In order to conduct research, the researcher has taken in consideration various temples and the facilities prevailing in these two sites. These sites are the prominent pilgrimage destination of Eastern Uttar Pradesh. In order to improve the infrastructure many developmental projects are in the process which actually can develop the spiritual and pilgrimage tourism in these places. It is evident that Pilgrimage Tourism is the key which actually helps pilgrims to develop spiritually. Pilgrimage, Spiritual and religious tourism, is a type of travel which is totally inspired because of some pious goals. These goals are relative as well. It could to lead to spiritual growth, happiness and to have peace and which leads to final destination in life that is self- actualization or Moksha. Pilgrimage tourism is one of the ways to reach this goal. In India people from all across the globe come for various reasons, out of which Spirituality and growth in this area is the most common. Therefore, a study on Prayagraj and Varanasi was conducted to identify and explore Pilgrims inclination towards Spiritual Tourism Development in these places. This study is an effort to discover visitor's inclinations, recognition & fulfillment with different type of services accessible at Varanasi and Prayagraj and also to find out the degree of fulfillment of pilgrims related to nourishment, transport offices, darshan/seva accessibility, books, etc In this study we used factor analysis to filter out the main variables and also to find the fundamental scope of pilgrim’s total satisfaction.